Development and Characterization of Co-Cr-Mo (F-75 alloy)/hydroxyapatite Composites Fabricated by Powder Metallurgy for Biomedical Applications - Nur Maizatul Shima Adzali (School of Materials Engineering, 2013)
This research reported the fabrication and characterization of F-75 alloy filled with HAP which have been prepared by powder metallurgy method. This study has focused on the effect of HAP addition into F-75 alloy and sintering temperature on the physical and mechanical properties of the F-75/HAP composites, its microstructure, and also its corrosion and bioactivity behaviour.